Permainan Tradisional Berbasis Outdoor Learning di Era Digital untuk Perkembangan Motorik Kasar Anak Usia Dini - Ahmad, Ocha Nabila Margareta; Ariani, Imel; Aniyawati, Aniyawati (Jurnal Caksana : Pendidikan Anak Usia Dini, 2025)
This study aims to describe and analyze the role of traditional outdoor learning-based games in optimizing gross motor development in early childhood in the digital era. The study employed a qualitative approach with a descriptive approach. The subjects consisted of 25 children from Group B of RA Bahrul Ulum, Rebang Tangkas Village, with the principal and three teachers serving as supporting informants. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing using source and technique triangulation. The results showed that implementing traditional games such as gobak sodor, engklek, and jump rope outdoors can improve children's gross motor skills, particularly muscle strength, balance, coordination, agility, and physical endurance. Furthermore, these activities positively impact children's socio-emotional development and contribute to the preservation of local cultural values. Traditional outdoor learning-based games have proven to be an effective and contextual learning alternative to balance the influence of digital technology, thus supporting the holistic development of early childhood.